Clinical, Histological, and Genetic Features of 25 Patients with Autosomal Dominant Progressive External Ophthalmoplegia (ad-PEO)/PEO-Plus Due to TWNK Mutations - Bermejo-Guerrero, Laura; de Fuenmayor-Fernández de la Hoz, Carlos Pablo; Serrano-Lorenzo, Pablo; Blázquez-Encinar, Alberto; Gutiérrez-Gutiérrez, Gerardo; Martínez-Vicente, Laura; Galán-Dávila, Lucía; García-García, Jorge; Arenas, Joaquín; Muelas, Nuria; Hernández-Laín, Aurelio; Domínguez-González, Cristina; et al. (Journal of clinical medicine, 2021)
Autosomal dominant mutations in the TWNK gene, which encodes a mitochondrial DNA helicase, cause adult-onset progressive external ophthalmoplegia (PEO) and PEO-plus presentations. In this retrospective observational study, we describe clinical and complementary data from 25 PEO patients with mutations in TWNK recruited from the Hospital 12 de Octubre Mitochondrial Disorders Laboratory Database. The mean ages of onset and diagnosis were 43 and 63 years, respectively. Family history was positive in 22 patients. Ptosis and PEO (92% and 80%) were the most common findings. Weakness was present in 48%, affecting proximal limbs, neck, and bulbar muscles. Exercise intolerance was present in 28%. Less frequent manifestations were cardiac (24%) and respiratory (4%) involvement, neuropathy (8%), ataxia (4%), and parkinsonism (4%). Only 28% had mild hyperCKemia. All 19 available muscle biopsies showed signs of mitochondrial dysfunction. Ten different TWNK mutations were identified, with c.1361T>G (p.Val454Gly) and c.1070G>C (p.Arg357Pro) being the most common. Before definitive genetic confirmation, 56% of patients were misdiagnosed (36% with myasthenia, 20% with oculopharyngeal muscle dystrophy). Accurate differential diagnosis and early confirmation with appropriately chosen complementary studies allow genetic counseling and the avoidance of unnecessary treatments. Thus, mitochondrial myopathies must be considered in PEO/PEO-plus presentations, and particularly, TWNK is an important cause when positive family history is present.